PENGARUH LINGKUNGAN KERJA DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PT. ENSEVAL PUTERA MEGATRADING JAKARTA - Rosmania; Arief Rachmawan Assegaf (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2024)
The purpose to analyze the influence of the work environment and organizational culture on employee performance at PT. Enseval Putera Megatrading Jakarta. Data were obtained through questionnaires that were distributed online via social media. The respondents to this study employees of PT. Putera Megatrading Jakarta Enseval selected through simple random sampling method. The analysis method uses simultaneously and partially regression. The results of this study found that: the work environment has a significant effect on the performance of PT. Enseval Putera Megatrading Jakarta, organizational culture has a significant effect on the performance of employees of PT. Enseval Putera Megatrading Jakarta, work environment and organizational culture have a significant effect on the performance of employees of PT. Enseval Putera Megatrading Jakar